Oxygen sensor element and method of manufacturing same

JP7643685B2Active Publication Date: 2025-03-11NAT UNIV CORP NAGAOKA UNIV TECH +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2021101193
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-06-17
Publication Date
2025-03-11
Estimated Expiration
2041-06-17

AI Technical Summary

Benefits of technology

【0013】 本発明によれば、センシング層のセンサ材料と、断熱層の断熱材との焼結挙動が近くなり、センシング層を断熱層で挟み込んだ積層構造を有する酸素センサ素子として同時焼成が可能となり量産性を確保できるとともに、センシング層における断熱性の向上により省電力化が可能となる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007643685000001
    Figure 0007643685000001
  • Figure 0007643685000002
    Figure 0007643685000002
  • Figure 0007643685000003
    Figure 0007643685000003
Patent Text Reader

Abstract

To provide an oxygen sensor element capable of saving power without damaging sensor characteristics.SOLUTION: There is provided an oxygen sensor element configured such that, an external surface of a ceramic sintered body is covered with heat insulation layers, the ceramic sintered body serving as a sensing layer which is formed of a composition LnBa2Cu3O7-δ(Ln is a rare earth element), and as the heat insulation layer, a heat insulation material whose composition is Ln2BaCuO5 is used, and to the composition, 20 mol% of LnBa2Cu3O7-δ is added. Therefore, since a sintering behavior of the heat insulation layer approximates to a sintering behavior of the sensing layer, interlayer detachment or generation of cracks can be prevented, and achieving a sandwich structure in which the sensing layer is sandwiched by the heat insulation layers can reduce a heat release amount from the sensing layer and achieve power saving.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an oxygen sensor element using a sintered ceramic body and a method for manufacturing the same. [Background technology]

[0002] In order to detect the oxygen concentration in a measurement atmosphere, for example, a gas, an oxygen sensor using a sintered ceramic body has been used. Such an oxygen sensor has a material composition, for example, LnBa2Cu3O 7-δ The sensor uses a composite ceramic made of a mixture of BaCuO and Ln2BaCuO5 (Ln is a rare earth element), and utilizes the hot spot phenomenon whereby part of the wire that makes up the sensor becomes red-hot when a voltage is applied.

[0003] It is desirable for oxygen sensors to be smaller, lighter, less expensive, and consume less power, from the viewpoints of the usage environment, sensing performance, etc. For example, Patent Document 1 discloses an oxygen sensor in which the hot spot of the sensor element is coated with a porous insulating material with low thermal conductivity, thereby reducing heat emission from the hot spot and reducing power consumption. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Japanese Patent Application Publication No. 10-73549 Summary of the Invention [Problem to be solved by the invention]

[0005] In order to maintain the oxygen detection function (sensing function) of an oxygen sensor, it is effective to have a configuration that maintains the temperature of the heat generating part. In Patent Document 1, a narrowed portion is formed at a specific position where a hot spot occurs in the wire material that constitutes the oxygen sensor, and the narrowed portion is covered with a heat insulating material. In addition, alumina (Al2O3), magnesia (MgO), yttria (Y2O3), and barium titanate (BaTiO3) are given as examples of heat insulating materials.

[0006] However, although forming a constriction at a specific position in the wire of an oxygen sensor has a certain effect in terms of power saving by making the wire thinner, it makes the wire more susceptible to melting due to hot spots that occur when the sensor is operated, which reduces the mechanical strength and makes it impossible to provide an oxygen sensor that is durable and reliable.

[0007] The heat insulating materials listed in Patent Document 1 are LnBa2Cu3O, which is the material of the sensor element. 7-δ (Ln represents a rare earth element, and δ represents oxygen nonstoichiometry) during firing, which not only deteriorates the sensor sensitivity but also makes it difficult to simultaneously fire the insulating material and the sensor element material, resulting in problems with poor mass production. Furthermore, the sintering behavior of these insulating materials is LnBa2Cu3O 7-δ Since the interface is easily peeled off, there are issues with ensuring the sensor sensitivity of the oxygen sensor and with mass production.

[0008] The present invention has been made in consideration of the above-mentioned problems, and an object of the present invention is to provide an oxygen sensor element that enables power saving during sensor operation without impairing the sensor characteristics as an oxygen sensor. [Means for solving the problem]

[0009] As a means for achieving the above object and solving the above problem, the present invention provides the following configuration: That is, the present invention is an oxygen sensor element made of a ceramic sintered body, which detects an oxygen concentration based on a current value or a resistance value when a voltage is applied to electrodes provided at both ends of the ceramic sintered body, and is characterized in that a heat insulating layer represented by the composition formula Ln2BaCuO5 (Ln is a rare earth element) is arranged so as to cover a predetermined portion of the outer surface of the ceramic sintered body excluding the electrodes.

[0010] For example, the thermal insulation layer has a composition formula of LnBa2Cu3O 7-δIt is characterized by adding a co-material represented by (Ln is a rare earth element, and δ represents oxygen non-stoichiometry). For example, it is characterized in that the addition amount a [mol%] of the co-material satisfies 0 < a ≤ 25. Also, for example, it is characterized in that the Ln is Nd (neodymium). Further, for example, it is characterized by having a laminated structure in which the outer surface of the ceramic sintered body excluding the electrode is sandwiched from both directions by the heat insulating layer, and a part of the ceramic sintered body is exposed. Also, for example, the thickness t1 [μm] in the lamination direction of the ceramic sintered body satisfies 10 ≤ t1 ≤ 200, and the thicknesses t2, t3 [μm] in the lamination direction of each of the heat insulating layers sandwiching the ceramic sintered body satisfy 50 ≤ (t2, t3) ≤ 400. For example, it is characterized by having a structure in which the entire outer surface of the ceramic sintered body excluding the electrode is covered with the heat insulating layer. Furthermore, for example, it is characterized in that the ceramic sintered body is formed into a linear body.

[0011] Also, the oxygen sensor of the present invention is characterized in that the above oxygen sensor element is used as an oxygen concentration detection element. For example, the oxygen sensor element is characterized in that it is housed in a protective tube having ventilation holes at both ends.

[0012] Furthermore, the present invention is a method for manufacturing an oxygen sensor element having a structure in which a predetermined portion of the outer surface of a ceramic sintered body as a sensing layer is covered with a heat insulating layer, comprising: a step of mixing raw materials of the ceramic sintered body and the heat insulating layer respectively to form respective slurries, and molding the slurries into sheet shapes to produce a first sheet member and a second sheet member; a step of cutting each of the first sheet member and the second sheet member into a predetermined size; a step of laminating the cut first sheet member and second sheet member so as to have a predetermined thickness, and forming a laminate in which the laminated first sheet member is sandwiched from the vertical direction by the laminated second sheet member; a step of cutting the laminate into a predetermined size and shape to produce a sensor element; a step of firing the sensor element; and a step of forming a pair of electrodes at both ends of the fired sensor element, and characterized in that the first sheet member and the second sheet member are fired simultaneously in the firing step. Effect of the Invention

[0013] According to the present invention, the sintering behavior of the sensor material of the sensing layer and the insulating material of the insulating layer are similar, making it possible to simultaneously sinter them into an oxygen sensor element having a laminated structure in which the sensing layer is sandwiched between insulating layers, ensuring mass productivity, and enabling power savings due to the improved insulating properties of the sensing layer. [Brief description of the drawings]

[0014] [Figure 1] 1 is a perspective view of the appearance of an oxygen sensor element according to an embodiment of the present invention; [Diagram 2] 4 is a flowchart showing, in chronological order, a manufacturing process for an oxygen sensor element according to an embodiment and an oxygen sensor using the oxygen sensor element. [Diagram 3] 1 is an external perspective view of a plate-shaped member formed by cutting and stacking a sheet member for a sensing layer and a sheet member for a heat insulating layer. FIG. [Figure 4] 1 is a perspective view of the appearance of an oxygen sensor using an oxygen sensor element according to an embodiment; [Diagram 5] FIG. 1 is a diagram showing evaluation result 1 of the sintering behavior of a test sample of an oxygen sensor element according to an embodiment. [Figure 6] FIG. 11 is a diagram showing evaluation results 2 of the sintering behavior of the test sample of the oxygen sensor element according to the embodiment. [Figure 7] FIG. 4 is a diagram showing the results of evaluating the temperature dependence of resistivity for a test sample of the oxygen sensor element according to the embodiment. [Figure 8] This is a phase diagram showing the possible coexistence of Nd211 and Nd123. [Figure 9] FIG. 1 is a diagram showing the evaluation results of the oxygen responsiveness as an oxygen sensor of a test sample of a conventional composition (Conventional Example 1) and a test sample according to an embodiment (Example 1). [Figure 10]FIG. 13 is a diagram showing the evaluation results of the oxygen responsiveness as an oxygen sensor for a test sample of a conventional composition (Conventional Example 2) and a test sample according to an embodiment (Example 2). [Figure 11] FIG. 11 is an external perspective view of an oxygen sensor element according to a modified example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] Hereinafter, an embodiment of the present invention will be described in detail with reference to the attached drawings. The oxygen sensor element according to this embodiment is made of a sintered ceramic body, and when connected to a power source and a current flows through it, the center of the sintered body heats up to a high temperature, and the heated area (called a hot spot) serves as the oxygen concentration detection area. The oxygen concentration is detected based on the value of the current flowing through the ceramic sintered body, which is the oxygen sensor element.

[0016] Fig. 1 is an external perspective view of an oxygen sensor element according to this embodiment. The oxygen sensor element 1 shown in Fig. 1 includes a sensing layer 5 having an oxygen detection function (oxygen sensing function), two heat insulating layers 4a, 4b sandwiching the sensing layer 5 from both sides (up and down), a pair of electrode portions 3a, 3b formed at both ends in the longitudinal direction of a laminate (sensor element) in which the sensing layer 5 and the heat insulating layers 4a, 4b are laminated, and lead wires 6a, 6b attached to the electrode portions 3a, 3b, respectively.

[0017] The sensing layer 5 is made of a sensor material having the composition LnBa2Cu3O 7-δ (Ln is a rare earth element, and δ is oxygen nonstoichiometry.) For example, if Ln is Nd (neodymium), the composition is NdBa2Cu3O 7-δ It consists of:

[0018] The heat insulating layers 4a and 4b are heat insulating and electrically insulating layers. For example, the composition Ln2BaCuO5 is Nd2BaCuO5 where Ln is Nd (neodymium) and 20 mol% NdBa2CuO3 is added as a co-material. 7-δ It is composed of a composition to which

[0019] In the following, the composition NdBa2Cu3O will be used as appropriate. 7-δ "Nd123", composition Nd2BaCuO5 "Nd211", composition Nd2BaCuO5 with 20mol% NdBa2Cu3O 7-δ The composition with added Nd211-20mol%Nd123 is described as "Nd211-20mol%Nd123".

[0020] In addition, although Nd (neodymium) is exemplified as the rare earth element Ln (rare earth element) of the oxygen sensor element material, any other rare earth element can be used. That is, as the rare earth element, for example, Sc (scandium), Y (yttrium), La (lanthanum), Sm (samarium), Eu (europium), Gd (gadolinium), Dy (dysprosium), Ho (holmium), Er (erbium), Tm (thulium), Yb (ytterbium), Lu (lutetium), etc. can be used.

[0021] Next, a method for manufacturing the oxygen sensor element according to the present embodiment and an oxygen sensor using the same will be described. Fig. 2 is a flow chart showing, in chronological order, the manufacturing process of the oxygen sensor element according to the present embodiment and the oxygen sensor using the oxygen sensor element.

[0022] In step S1 of FIG. 2, a raw material for the oxygen sensor element is prepared using a composition of NdBa2Cu3O 7-δ For example, Nd2O3, BaCO3, and CuO are weighed using an electronic balance or the like and mixed together to obtain a composition of Nd2BaCuO5 (Nd211: raw material 2) with Nd123: raw material 1.

[0023] In step S2, the raw materials 1 and 2 of the oxygen sensor element weighed and mixed in step S1 are pulverized in a ball mill. The pulverization can be performed by a solid phase method such as a bead mill using beads as the pulverization medium, or a liquid phase method.

[0024] In the next step S3, the pulverized materials (powders of raw materials 1 and 2) are heat-treated (calcined) in air at 900°C for 5 hours. Calcination is a process for adjusting reactivity and particle size. The calcination temperature may be 880 to 970°C, and more preferably 900 to 935°C.

[0025] The calcined raw materials 1 and 2 are pulverized by a ball mill or the like to make the particles uniform, and then a slurry is prepared in step S4. Here, the calcined raw materials are mixed with a vehicle that is a mixture of a binder resin (e.g., polyvinyl butyral (PVB)) and a solvent (e.g., toluene) to prepare a slurry.

[0026] Specifically, a first slurry is prepared by mixing calcined powder of raw material 1 (Nd123) with a vehicle, and a second slurry is prepared by mixing calcined powder (Nd211-20mol%Nd123) of raw material 2 (Nd211) with a vehicle, in which 20mol% Nd123 has been added.

[0027] In the subsequent step S5, the first slurry and the second slurry are each formed into a sheet having a thickness of 30 μm, for example by a doctor blade method, to produce a first sheet member to be used for the sensing layer described above and a second sheet member to be used for the insulating layer described above.

[0028] The method for forming the slurry into a sheet shape may be, for example, uniaxial pressing, hydrostatic pressing, hot pressing, printing, or thin film forming, whereby a plate-shaped member (press-molded body) of a predetermined thickness is produced by applying a pressing pressure. In particular, the dipping, printing, and thin film forming methods are applicable to the second sheet member used in the heat insulating layer.

[0029] In step S6, the first sheet member and the second sheet member produced in step S5 are laminated to produce a laminated sheet (laminate) 20 shown in Fig. 3. Specifically, after cutting each of the first and second sheet members to a size of, for example, L1 (100 mm) x L2 (100 mm), the first sheet member is laminated to a thickness t1 of, for example, 30 µm as shown by reference numeral 15 in Fig. 3 to form a sensing layer, and the second sheet members sandwiching the first sheet member from above and below are laminated to have thicknesses t2 and t3 of, for example, 160 µm to form heat insulating layers 14a and 14b.

[0030] In addition, when focusing on the characteristics of the oxygen sensor element, the thicknesses of the laminated sensing layer and heat insulating layer are not limited to the above-mentioned thicknesses. For example, if the thickness t1 of the sensing layer is smaller than 10 μm, the resistance value becomes too high, making it difficult to ensure the amount of heat generated when a hot spot occurs. In addition, the increase in current density becomes significant, deteriorating durability. On the other hand, if the thickness t1 is larger than 200 μm, the power consumption becomes too large due to the increase in the current value when the oxygen sensor is operated. For this reason, the preferred thickness t1 of the sensing layer is 10 to 200 μm, and the more preferred thickness t1 is 30 to 120 μm.

[0031] If the thicknesses t2, t3 of the heat insulating layer are less than 50 μm, the heat insulating effect is reduced, and if they are more than 400 μm, the response speed of the oxygen sensor is affected. Therefore, the preferred thickness of the heat insulating layer is 50≦(t2, t3)≦400 μm, and the more preferred thickness is 100≦(t2, t3)≦250 μm.

[0032] In step S7, dicing is performed. Specifically, the laminated sheet (laminate) shown in Fig. 3 laminated in step S6 is cut into a rod shape having a cross-sectional dimension of 0.35 mm x 0.35 mm and a length of 5 mm according to the size and shape of the oxygen sensor described below.

[0033] In step S8, the oxygen sensor element after dicing is debindered, and the oxygen sensor element is sintered in air, for example, at 980°C for 10 hours. The sintering can be performed at a temperature range of 900 to 1020°C, and the sintering temperature may be changed depending on the composition. In addition, an annealing treatment may be performed after the sintering.

[0034] In step S9, silver (Ag) is dip-applied to both ends of the oxygen sensor element and dried at 150° C. for 10 minutes to form electrodes 3a and 3b as shown in Fig. 1. In step S10, a silver (Ag) wire of, for example, φ0.1 mm is attached to the electrodes formed in step S9 by a bonding method such as wire bonding and dried at 150° C. for 10 minutes. Then, in step S11, the terminal electrodes thus formed are baked at, for example, 670° C. for 20 minutes (electrode baking).

[0035] The material of the electrodes and wires is not limited to the above-mentioned silver (Ag), but may be, for example, gold (Au), platinum (Pt), nickel (Ni), tin (Sn), copper (Cu), or a resin electrode. In addition, the electrodes may be formed using a film deposition method such as printing or sputtering. Furthermore, the electrical characteristics of the oxygen sensor element manufactured through the above-mentioned process may be evaluated, for example, by a four-terminal method.

[0036] In step S12, the oxygen sensor element manufactured in the above steps is inserted into a protective tube (cylindrical glass tube) 24 made of heat-resistant glass and functioning as a protective member for the oxygen sensor element 1, as shown in Fig. 4. After insertion, each end of the lead wires of the oxygen sensor element 1 is connected to metallic conductive caps (bases) 23a, 23b fitted onto both ends of the protective tube 24, for example, by lead-free solder.

[0037] The specific configuration of the oxygen sensor in which the oxygen sensor element is housed within the protective tube as described above will be described later.

[0038] Next, the results of evaluation of the sensor characteristics and the like measured on a test sample of the oxygen sensor element according to this embodiment will be described.

[0039] <Evaluation results of sintering behavior> The oxygen sensor element according to this embodiment has a structure (sandwich structure) in which the sensing layer is sandwiched between two insulating layers made of different materials from above and below. Therefore, when these layers are fired simultaneously, there is a concern that delamination or the like may occur due to differences in sintering behavior.

[0040] Therefore, the sintering behavior of the test sample of the oxygen sensor element according to this embodiment was measured by thermomechanical analysis (TMA). The results are shown in Figures 5 and 6. In Figures 5 and 6, the horizontal axis is temperature [°C] and the vertical axis is displacement [%].

[0041] [Evaluation result 1] In FIG. 5, the characteristic indicated by the reference numeral 51 is Nd123 (composition NdBa2Cu3O 7-δ The characteristic indicated by the reference numeral 52 is the measurement result of the sintering behavior of Nd211 (composition Nd2BaCuO5), and the characteristic indicated by the reference numeral 53 is the measurement result of the sintering behavior of Nd211-20mol%Nd123 (composition Nd2BaCuO5 with 20mol% NdBa2Cu3O 7-δ The results are shown in Table 1.

[0042] From the results of measuring the sintering behavior by TMA, it can be seen that the sintering behavior of the material in which 20 mol% of Nd123 is added to Nd211 approaches that of Nd123. This indicates that the sintering temperature of Nd211 is higher than that of Nd123, but is shifted to the lower side by adding Nd123.

[0043] Therefore, even if the sensing layer made of Nd123 and the insulating layer made of Nd211-20mol%Nd123 are fired simultaneously, their sintering behavior is the same, so stress is unlikely to occur at the interface. As a result, since there is no distortion or stress, it is possible to prevent the occurrence of delamination and cracks, which improves the mass productivity of oxygen sensor elements.

[0044] The reason why no delamination occurred is believed to be that the materials of the heat insulating layer and the sensing layer are both porous, which keeps the sintering density low. In addition, because the heat insulating layer and the sensing layer are porous, they do not affect the sensing function of the oxygen sensor element.

[0045] [Evaluation result 2] In addition, the sintering behavior of the sensing layer was measured for compositions with different amounts of Nd substituted. 1+x Ba 2-x CuO 7-δ In this case, the Nd substitution amount x is set to 0.4. 1.4 Ba 1.6 CuO 7-δ (This composition is referred to as Nd123_x-0.4.) The sintering behavior was measured by thermomechanical analysis (TMA). The results are shown in Figure 6.

[0046] As shown by the dashed line 54 in Fig. 6, the material with the composition Nd123_x-0.4 was able to bring the sintering behavior closer to that of Nd211-20mol%Nd123 (indicated by reference symbol 53) while maintaining the resistivity described below. Nd123_x-0.4 has a composition in which Nd123, the material of the sensing layer, is substituted with Nd, indicating that the sintering temperature shifts to the higher temperature side when Ba is substituted with Nd.

[0047] From the above evaluation results 1 and 2, from the viewpoint of simultaneous firing, etc., it is considered that the optimal combination for the oxygen sensor element is Nd123_x-0.4, which also has moisture resistance as the material for the sensing layer, and Nd211-20mol%Nd123 as the material for the heat insulating layer, and that this combination will further improve mass productivity of the oxygen sensor element.

[0048] In addition, although the material of the sensing layer (Nd123_x - 0.4) and the material of the heat insulation layer (Nd211 - 20 mol% Nd123) have equivalent reactivity, it was confirmed that even when they are laminated in a sandwich structure, they do not react with each other to form a different material. Furthermore, referring to the phase diagram shown in Fig. 8, it can be seen that Nd211 and Nd123 can coexist and do not react during firing.

[0049] Note that in the above, as the heat insulation layer, a material obtained by adding 20 mol% of LnBa2Cu3O as a co-material to the composition Ln2BaCuO5 was exemplified. However, if the addition amount a [mol%] of this co-material is in the range of 0 < a ≤ 25, the desired heat insulation and insulation effects can be obtained. If added in excess of 25 mol%, a conductive path due to LnBa2Cu3O is formed within the heat insulation layer due to percolation, resulting in impairment of the insulation function and an increase in power consumption. 7-δ 7-δ

[0050] <Evaluation Results of Temperature Dependence of Resistivity> Fig. 7 shows the results of evaluating the temperature dependence of the resistivity for a test sample of the oxygen sensor element according to this embodiment. In Fig. 7, the horizontal axis represents temperature [°C] and the vertical axis represents resistivity [Ωcm].

[0051] As shown in Fig. 7, regarding the material of the heat insulation layer, Nd211 indicated by reference numeral 62 had a higher resistivity than Nd211 - 20% Nd123 indicated by reference numeral 63. Both Nd211 and Nd211 - 20% Nd123 exhibit semiconductor characteristics in which the resistivity decreases as the temperature increases.

[0052] On the other hand, it can be seen that Nd123, which is the material of the sensing layer indicated by reference numeral 61 in Fig. 7, has a low resistivity and is a material through which current easily flows. Focusing on 900°C, which is the actual operating temperature of the oxygen sensor, since Nd211 - 20% Nd123 has a resistance value two digits or more higher than that of Nd123, it can be seen that the insulation function is sufficiently ensured even when Nd123 is added as a co-material to Nd211.

[0053] ​​That is, in the oxygen sensor element, almost no current flows through the heat insulating layer made of Nd211-20% Nd123, and the insulating function for the sensing layer is not lost, so there is no effect on the sensor output.

[0054] <Evaluation results of oxygen responsiveness> 9 shows the results of evaluating the oxygen responsiveness as an oxygen sensor for a test sample of conventional composition and a test sample according to this embodiment as Example 1. The test sample of conventional composition (Conventional Example 1) does not have a heat insulating layer and is made of only Nd123, and is an element of the same dimensions as Example 1.

[0055] Here, for each test sample, the environment was standard air (oxygen concentration 21%) during period T1 in Fig. 9, then switched to an environment with an oxygen concentration of 1% during the following period T2, and then switched to standard air (oxygen concentration 21%) during period T3. In Fig. 9, the horizontal axis is time [seconds], and the vertical axis is current change (sensitivity) [%].

[0056] 9, it can be seen that the change in sensor output (responsiveness) of both Example 1 and Conventional Example 1 is 30%, and that there is no significant difference in oxygen responsiveness between the test sample of Example 1 and the sample of Conventional Example 1. In addition, the rise and fall of the current change at each change point of the oxygen concentration from time T1 to T2 to T3 is also steep, which shows that there is no difference in oxygen responsiveness between the test sample of Example 1 and the test sample of Conventional Example 1 (the sensor output and response speed are equivalent).

[0057] For each test sample of Example 1 and Conventional Example 1, for example, power consumption was calculated from the current-voltage characteristics, and Conventional Example 1 was 0.47 W, whereas Example 1 was able to reduce the power consumption to 0.40 W. Therefore, it was found that Example 1 can reduce the power consumption by about 1 / 5 compared to Conventional Example 1.

[0058] FIG. 10 shows the results of evaluating the oxygen responsiveness as an oxygen sensor for Example 2, in which the composition Nd123_x-0.4, in which Nd123 is substituted with Nd, is used as the sensing layer. The test sample of the conventional composition (Conventional Example 2) is made of only Nd123x-0.4 without forming a heat insulating layer, and is an element of the same dimensions as Examples 1 and 2. It can be seen that Example 2 also has the same oxygen responsiveness as Example 1 and Conventional Example 2. In addition, when the power consumption of Example 2 is calculated in the same manner as Example 1, etc., it is 0.61 W for Conventional Example 2, whereas it is 0.48 W for Example 2. Therefore, it can be seen that Example 2 can also achieve power saving without impairing its sensor characteristics (sensor output, response speed).

[0059] Considering the mechanical strength, mass production, etc., of the oxygen sensor element, there is a limit to the power saving achieved by reducing the current value by thinning the element. Therefore, the oxygen sensor element according to this embodiment has a sandwich structure in which the sensing layer is sandwiched between heat insulating layers, thereby reducing the amount of heat dissipated from the element and achieving power saving. In particular, since heat dissipation by radiation is proportional to the fourth power of the element surface temperature according to the Stefan-Boltzmann law, reducing the surface temperature by forming a heat insulating layer is effective. As a result, it becomes possible to reduce the size of the battery used to operate the oxygen sensor using the oxygen sensor element, improving the portability of the oxygen sensor as a device.

[0060] <About oxygen sensors> In an oxygen sensor using the oxygen sensor element according to this embodiment, a heat generating portion (hot spot) in the center of the oxygen sensor element serves as an oxygen concentration detection portion. The oxygen sensor 10 shown in Fig. 4 has a structure in which the oxygen sensor element 1 is housed inside a cylindrical glass tube 24 made of heat-resistant glass, which is a protective member for the oxygen sensor element 1. Metallic conductive caps (bases) 22a, 22b made of, for example, copper (Cu) are fitted to both ends of the glass tube 24 to electrically connect the oxygen sensor 10 to the outside.

[0061] Silver (Ag) wires (leads 6a, 6b in FIG. 1) attached to both ends of the oxygen sensor element 1 are electrically connected to the conductive caps 22a, 22b with lead-free solder, and the oxygen sensor element 1 is arranged so that the longitudinal direction of the oxygen sensor element 1 is in the axial direction of the glass tube 24, thereby preventing the oxygen sensor element 1 from coming into contact with the glass tube 24.

[0062] The conductive caps 22a, 22b have ventilation holes 23a, 23b on the end faces thereof, respectively, so that the gas to be measured (oxygen) smoothly flows into the glass tube 24, and the oxygen sensor element 1 is exposed to the gas, thereby enabling the oxygen concentration in the atmosphere to be accurately measured.

[0063] The glass tube 24 of the oxygen sensor 10 has, for example, a diameter of 5.2 mm, a length of 20 mm, and a vent hole diameter of 2.5 mm, and the oxygen sensor element 1 having the above-mentioned dimensions (0.35 mm × 0.35 mm × 5 mm) can be replaced via the vent holes 23a, 23b of the glass tube 24.

[0064] The protective member for the oxygen sensor element 1 may be, for example, a ceramic case, a resin case, etc., other than the above-mentioned glass tube. The silver (Ag) wires 6a, 6b attached to the oxygen sensor element 1 and the conductive caps 22a, 22b may be connected by a joining method such as lead soldering, welding, or crimping.

[0065] In addition, although not shown in the drawings, an oxygen sensor using the oxygen sensor element according to this embodiment is configured such that, when a predetermined voltage is applied to the oxygen sensor from a power source, a current corresponding to the ambient oxygen concentration flows through the oxygen sensor element, and the oxygen concentration of the atmosphere to be measured is measured based on the value of that current measured by an ammeter.

[0066] The structure and shape of the oxygen sensor element are not limited to a rod-like shape having a sandwich structure such as the oxygen sensor element 1 shown in Fig. 1. For example, as in the oxygen sensor element 70 shown in Fig. 11, the entire outer surface of a cylindrical ceramic sintered body 75 made of Nd123 is covered with a heat insulating layer 74 made of Nd211-20mol%Nd123, a pair of electrodes 73a, 73b are formed at both ends of the sensor element in the longitudinal direction, and lead wires 76a, 76b are attached to the electrode parts, respectively, so that the overall shape of the sensor element may be cylindrical.

[0067] 11, power consumption can be reduced by reducing the amount of radiative heat released from the ceramic sintered body 75 due to the heat insulating layer 74. In addition, the sensing performance of the oxygen sensor element 70 is not hindered by the heat insulating layer 74 because the heat insulating layer 74 is porous.

[0068] As described above, the oxygen sensor element according to this embodiment has the composition LnBa2Cu3O 7-δ The outer surface of the ceramic sintered body as the sensing layer made of (Ln is a rare earth element) is covered with a heat insulating layer. The heat insulating layer is made of a heat insulating material having a composition of Ln2BaCuO5, and the composition contains 20 mol% of LnBa2Cu3O. 7-δ was added.

[0069] As a result, the sintering behavior of the sensor material of the sensing layer and the insulating material of the insulating layer becomes similar, so that no peeling occurs at the interface during firing and the strength is improved, ensuring mass productivity of the oxygen sensor element. Furthermore, a laminated structure in which the sensing layer is sandwiched between the insulating layers can be simultaneously fired, and for example, when the oxygen sensor element is incorporated into a protective member such as a glass tube, the sensor portion does not need to be directly gripped, making it easier to manufacture the oxygen sensor and improving the mass productivity of the oxygen sensor.

[0070] Furthermore, the sensor material and the insulating material can coexist and no reaction occurs during firing. In addition, the laminated structure minimizes exposure of the sensing layer to the outside, suppressing radiant heat and making the sensor resistant to disturbances such as external gases. At the same time, the sensor sensitivity as an oxygen sensor element using the hot spot phenomenon can be maintained. At the same time, improved insulation makes it possible to reduce power consumption.

[0071] In addition, the insulating material of the insulating layer has the composition LnBa2Cu3O 7-δ The addition of this material is expected to improve the heat cycle properties during sensor use. [Explanation of symbols]

[0072] 1,70 Oxygen sensor element 3a,3b,73a,73b Electrode part 4a, 4b, 74 Thermal insulation layer 5,15 Sensing layer 6a, 6b, 76a, 76b Lead wire 10 Oxygen Sensor 22a, 22b Conductive cap 23a, 23b Ventilation holes 24 Glass tube 75 Sintered ceramics

Claims

1. An oxygen sensor element made of a sintered ceramic body, which detects an oxygen concentration based on a current value or a resistance value when a voltage is applied to electrodes provided at both ends of the element, The ceramic sintered body is coated with a composition of formula Ln 2 BaCuO 5 (Ln is a rare earth element).

2. The thermal insulation layer has the composition formula LnBa 2 Cu 3 O 7-δ 2. The oxygen sensor element according to claim 1, further comprising a co-material represented by the formula: (Ln represents a rare earth element, and δ represents oxygen non-stoichiometry).

3. 3. The oxygen sensor element according to claim 2, wherein the amount a [mol %] of the common material is in the range of 0<a≦25.

4. 4. The oxygen sensor element according to claim 1, wherein the Ln is Nd (neodymium).

5. The oxygen sensor element according to any one of claims 1 to 4, characterized in that the insulating layers sandwich the outer surface of the ceramic sintered body, excluding the electrodes, from both sides, and the ceramic sintered body has a laminated structure in which a part of the ceramic sintered body is exposed.

6. The oxygen sensor element according to claim 5, characterized in that the thickness t1 [μm] of the ceramic sintered body in the stacking direction is 10≦t1≦200, and the thicknesses t2, t3 [μm] of each of the insulating layers sandwiching the ceramic sintered body in the stacking direction are 50≦(t2, t3)≦400.

7. 5. The oxygen sensor element according to claim 1, wherein the entire outer surface of the sintered ceramic body, excluding the electrodes, is covered with the heat insulating layer.

8. 8. The oxygen sensor element according to claim 1, wherein the ceramic sintered body is formed into a linear body.

9. 9. An oxygen sensor comprising the oxygen sensor element according to claim 1 as an element for detecting an oxygen concentration.

10. 10. The oxygen sensor according to claim 9, wherein the oxygen sensor element is accommodated in a protective tube having air holes at both ends.

11. A method for manufacturing an oxygen sensor element having a structure in which a predetermined portion of an outer surface of a ceramic sintered body serving as a sensing layer is covered with a heat insulating layer, comprising the steps of: a step of mixing raw materials for the ceramic sintered body and the heat insulating layer to form slurries each in a sheet shape to prepare a first sheet member and a second sheet member; cutting each of the first sheet member and the second sheet member to a predetermined size; a step of stacking the cut first sheet member and the cut second sheet member to a predetermined thickness, and sandwiching the stacked first sheet member between the stacked second sheet members from above and below to form a laminate; cutting the laminate into a predetermined size and shape to produce a sensor element; sintering the sensor element; forming a pair of electrodes on both ends of the fired sensor element; Equipped with A method for manufacturing an oxygen sensor element, comprising the steps of: firing the first sheet member and the second sheet member simultaneously in the firing step.

Citation Information

Patent Citations

  • Self-heating type oxygen sensor

    JP1998073549A

  • Oxygen sensor

    JP2007085816A

  • Gas sensor and manufacturing method therefor

    JP2019168366A

  • Gas sensor and method for manufacturing the same

    JP2019168367A